Studies on Canning of Mackerel Fillets in Oil - SARALAYA, K V; PARASHURAM, P; RAI, B S (Fishery Technology, 1975)
Canning operations suitable for packing mackerel ( Rastrelligerkanagurta) in the form of skinless and boneless fillets in oilwere studied and the process standardised. The technique oflye peeling for skin removal could be successfully applied.The storage life of the final product was tested over a periodof mie year and found to be quite comparable to othersimilar fish products.